Incidence of pathologic postobstructive diuresis after resolution of ureteropelvic junction obstruction with a normal contralateral kidney. Issue 6 (December 2018) - Roth, J.D.; Lesier, J.D.; Casey, J.T.; Szymanski, K.M.; Whittam, B.M.; Misseri, R.; Rink, R.C.; Cain, M.P.
Summary: Introduction: Postobstructive diuresis (POD) after unilateral pyeloplasty or percutaneous nephrostomy (PCN) tube insertion for ureteropelvic junction obstruction (UPJO) in patients with a normal contralateral kidney is not well described. Objective: The objective of this study was to determine the incidence and characteristics of POD after relief of unilateral UPJO in patients with a normal contralateral kidney. Study design: Children who underwent a unilateral pyeloplasty or PCN for UPJO from 2010 to 2017 with a normal contralateral kidney were retrospectively reviewed. Postobstructive diuresis was defined as urine output (UO) of >300% of expected UO. Patients with a solitary kidney or those who underwent bilateral pyeloplasty or bilateral PCN tube placement were excluded. Results: Out of 396 children meeting inclusion criteria, seven (1.8%) developed POD (4 after pyeloplasty and 3 after PCN tube placement). Median age at intervention was 1.7 years (range 11 days–18 years); median weight was 11.4 kg (range 3.7–54.2 kg). Postobstructive diuresis was more likely to occur in patients with grade 4 hydronephrosis (3.0%) and larger kidneys and if a PCN tube was placed before pyeloplasty. There was no significant difference in age, gender, kidney laterality, or function between those who developed POD and those who did not. Postobstructive diuresis was managed with additional intravenous fluids and electrolyte monitoring. Median initial postprocedure UO was 5.9 mg/kg/hr (range 3.2–10.0 mg/kg/hr). In five children who underwent PCN in whom UO could be differentiated between kidneys, median initial postprocedure UO was 6.1 mg/kg/hr (range 2.5–9.1 mg/kg/hr) from the affected side and 0.8 mg/kg/hr (range 0.4–0.9 mg/kg/hr) from the unaffected side. The median length of time to resolution of POD was 3 days (range 2–4 days). One patient developed significant acidosis and lethargy that improved with intravenous fluid management. Mild hyponatremia developed in two, hypokalemia in one, hypophosphatemia in one, acidosis in one, and hypoglycemia in 1 patient. Discussion: A low but clinically significant risk of POD occurring after relief of unilateral UPJO in children with a normal contralateral kidney is described. Limitations include retrospective analysis and small sample size due to the rarity of the condition. Conclusion: Postobstructive diuresis after decompression of UPJO in patients with a normal contralateral kidney is a rare event (1.8%). However, POD does occur, and patients should be carefully monitored after these procedures given the potential for significant dehydration and electrolyte disturbances. Table Predictors of postobstructive diuresis. Factors affecting postobstructive diuresis No POD (N = 389) POD (N = 7) P -value Grade of hydronephrosis of the affected kidney before intervention, # (%)  3 or lower 166 (42.7%) 0 (0%) 0.04  4 223 (57.3%) 7 (100.0%)   Median size differential of the affected compared to the unaffected kidney, cm (IQR) +1.4 (+2.4 to −0.8) +4.4 (+5.6 to −2.5) 0.02 Median size ratio of the affected to the unaffected kidney (IQR) 1.2 (1.1–1.4) 1.8 (1.5–2.1) 0.01 Need for nephrostomy tube before pyeloplasty, # (%) 23 (5.9%) 3 (42.9%) <0.01 IQR, interquartile range; POD, postobstructive diuresis.